2002
DOI: 10.1074/jbc.m109932200
|View full text |Cite
|
Sign up to set email alerts
|

Kinked Collagen VI Tetramers and Reduced Microfibril Formation as a Result of Bethlem Myopathy and Introduced Triple Helical Glycine Mutations

Abstract: Mutations in the genes that code for collagen VI subunits, COL6A1, COL6A2, and COL6A3, are the cause of the dominantly inherited disorder, Bethlem myopathy. Glycine mutations that interrupt the Gly-X-Y repetitive amino acid sequence that forms the characteristic collagen triple helix have been defined in four families; however, the effects of these mutations on collagen VI biosynthesis, assembly, and structure have not been determined. In this study, we examined the consequences of Bethlem myopathy triple heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 31 publications
(35 reference statements)
5
49
0
Order By: Relevance
“…Collagen is crucial to the bone matrix, but the most common bone collagen is Collagen type 1, with far less being known about COL6A1, though its mutations are linked to muscularskeletal defects such as Bethlam myopathy and Ulrich Congentical Muscular Distrophy [51][52][53][54]. Interestingly, a recent secretome analysis identified COL6A1 as a strongly upregulated protein in the conditioned media of metastatic, as compared to non-metastatic lung cancer cell lines [55].…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…Collagen is crucial to the bone matrix, but the most common bone collagen is Collagen type 1, with far less being known about COL6A1, though its mutations are linked to muscularskeletal defects such as Bethlam myopathy and Ulrich Congentical Muscular Distrophy [51][52][53][54]. Interestingly, a recent secretome analysis identified COL6A1 as a strongly upregulated protein in the conditioned media of metastatic, as compared to non-metastatic lung cancer cell lines [55].…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…In the first case, mutations towards the N terminal region of the triple helix may cause kinking of the tetramers in the normally straight supercoiled triple helical region, thus reducing their ability to form microfibrils 127 and exerting a dominant negative effect. Baker et al 124 confirmed that the majority of the Bethlem myopathy mutations occur toward the N-terminal end of the triple helix, that is a critical region of the collagen VI monomer (α1:α2:α3) is critical for efficient dimer, tetramer, and microfibril assembly.…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
“…For example, a heterozygous nonsense mutation causing an alpha-1 premature stop codon and a decrease of available alpha-1 chains consequently reduces production and secretion of collagen VI 126 . otherwise, a heterozygous missense mutation interrupting the repetitive amino acid sequence (glycine mutation) that forms the characteristic collagen triple helix either in the alpha-1or alpha-2 chains does not affect collagen VI intracellular monomer, dimer, and tetramer assembly or secretion, but the mutant tetramers are anomalous (kinked) and the extracellular microfibrils are functionally deficient 127 . Patients reported with a heterozygous in-frame deletion in the triple-helical domain resulting in exon skipping in the Col6A1 gene have either a typical clinical picture with finger contractures 125 or a course more severe than that commonly reported 128 .…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations